Sweet people are everywhere - Walker, Alice, 1944- (Tra Publishing, 2021)
"Sweet People Are Everywhere, an illustrated picture book featuring a poem by internationally renowned writer and activist Alice Walker, is a powerful celebration of humanity. The poem addresses a young boy getting his first passport, taking the boy--and the reader--on a journey through a series of countries around the globe where 'sweet people' can be found"--